The Signaling Effect of Corporate Social Responsibility in Emerging Economies - Su, W.; Peng, Mike; Tan, W.; Cheung, Y. (Springer Netherlands, 2016)
What signals do firms in emerging economies send to stakeholders when they adopt corporate social responsibility (CSR) practices? We argue that in emerging economies, firms that adopt CSR practices positively signal investors that their firms have superior capabilities for filling institutional voids. From an institution-based view, we hypothesize that the institutional environment moderates the signaling effect of CSR on a firm’s financial performance. Based on a sample of firms from ten Asian emerging economies, we find a positive relationship between CSR practices and financial performance. This positive relationship is stronger in the less developed capital market than in the more developed one. The financial benefits of CSR practices are also more salient in the low information diffusion market than in the high one. We emphasize that signaling theory and the institution-based view can jointly contribute to the CSR literature.